(untitled) (Journal of Philosophy Culture and Political Science, 2022)
This article focus not only on the importance of the concept of fashion in the daily life of every person but its impact on the spiritual world and studies the impact on cultural, ethical and other quality properties of a person by influencing his (her) inner world. It is impossible to imagine modern society without fashion, because it significantly affects the attitude of a person to himself and even others, not only with this it acts as a factor that largely determines the behavior of individuals and social groups. The fashion industry is constantly evolving, occupying a very strong place in everyday life. As long as there are people and there is life, the concept of fashion will always find its place in our lives. Fashion is also a kind of communication system, a way of self-expression. Fashion designers give people a choice to express themselves. Fashion is a complex socio-cultural phenomenon, a mechanism of social and cultural regulation, closely related to the main values and tendencies of society’s development. This article is devoted to the analysis of values and trends in fashion behavior. Keywords: fashion, society, ethics, culture, aesthetics.